Implementing international environmental agreements in Russia - Hønneland, Geir (Issues in environmental politics., 2003)
"This exciting book is the first systematic study of how international environmental agreements are transformed into political action in Russia. Using three illuminating case studies on the implementation process in the fields of fisheries management, nuclear safety and air pollution control, this book fills an important gap in existing literature. While the focus in current social science debate on international environmental regimes is accumulating knowledge on 'implementing activities' at both national and international level, this book goes one step further and examines implementation at national and regional level. This topic is of great theoretical relevance to the study of environmental politics since some of the main sources of environmental degradation in Europe are to be found in the Russian Federation. It is also of relevance to the more general debate on contemporary Russian politics and offers valuable new material on regional politics in Russia. With its emphasis on the politics of environmental and resource management, it continues the description and discussion of political processes where most accounts of Russian politics tend to stop. This book will be invaluable for undergraduates, postgraduates and academics studying environmental politics and Russian politics at regional and national level"--Publisher's description